Energy demand substitution from biomass to imported kerosene: Evidence from Tanzania. (July 2019) - Olabisi, Michael; Tschirley, David L.; Nyange, David; Awokuse, Titus
Abstract: We analyze domestic household energy demand and use patterns in Tanzania, using a detailed household survey of purchase transactions, a multivariate probit model, and the QUAIDS modeling framework. The main fuel sources that we study are kerosene, charcoal, and firewood. These three accounted for 96.5% of spending on energy by households. Charcoal and firewood are used for cooking while kerosene is used for lighting and cooking. Kerosene is almost exclusively imported, while charcoal and firewood are produced domestically. These fuel sources are important, given the impacts of wood harvesting on the environment and kerosene imports on public finances. We find a statistically significant response in kerosene demand to charcoal prices, suggesting a pattern of substitution, but no strong substitution relationships between other fuel pairs. These results, which we use in a simulation of tariff change, imply that policies centered on price changes may not be effective in changing consumer behavior unless alternative sources of energy are readily accessible. Highlights: Most energy spending is Tanzania is on imported kerosene, charcoal, and firewood. Policies for an energy transition must reflect how consumers respond to prices, or not. The price elasticity of substitution for most pairs of fuel types is low. Fuels act more like substitutes in hypothetical scenarios where households can buy all fuel types. Price-based policies for fuel demand may be ineffective if access to fuel options is limited.